Cinematic nihilism : encounters, confrontations, overcomings - Marmysz, John, 1964- (Edinburgh : Edinburgh University Press, 2017)
Through case studies of popular films, including Prometheus, The Dark Knight Rises, Dawn of the Dead and The Human Centipede, this book re-emphasises the constructive potential of cinematic nihilism.
Scotland as a site of nihilistic sacrifice -- The myth of Scotland as nowhere in particular -- Monstrous masses: the human body as raw material -- From night to survival: nihilism and the living dead -- The lure of the mob: cinematic depictions of skinhead authenticity -- Cultural change and nihilism in the Rollerball films -- The abject self: apocalyptic consequences of self-discovery in Fight Club -- Rooting for the fascists in Avatar -- Yukio Mishima and the return to the body.
Includes bibliographical references (pages 203-208), filmography (pages 209-210) and index.
Print version record.
JSTOR
Keywords: Nihilism (Philosophy) in motion pictures; PERFORMING ARTS -- Reference; LITERARY CRITICISM -- General; Nihilism (Philosophy) in motion pictures